Long-term effects of childbearing postponement - Dalkhat M. Ediev (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2005)
Long-term consequences of childbearing postponement for the population size are considered. General relations are obtained, which imply that the cohort NRR, the final generation length, and dynamics of the number of genealogical lines determine the final population trend. The period fertility rates are not relevant to ultimate population size in the case of stationary population and have only moderate effect when cohort NRR differs from unity. Relations obtained are also of value for formal demography and can be applied to the fertility transition modeling, population forecasting, and population genetics.
Keywords: 300; Childbearing postponement; genealogical lines; cohort rates; long-term population dynamics; Familienplanung; Fertilität; Bevölkerungsentwicklung; Kohortenanalyse